TINJAUAN SOSIOLOGI SASTRA NOVEL AYAH KARYA ANDREA HIRATA DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR SASTRA DI SMA - Nilawijaya, Rita; Inawati, Inawati (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2020)
This study aims to describe the social values ​​contained in Andrea Hirata's Father's novel and its implementation as literary teaching material in high school. The data source is Father Hirata's novel Andrea Hirata. Data collection techniques in this study using library technique, listen, and note. The data analysis technique in this study is to use dialectical techniques. The validity of the data for this study is to use data triangulation. The results of the research show that the theme of Father's novel is the struggle of a child who wants to provide happiness to his parents, especially to a father figure; the setting of this novel is in the Bangka Belitung area, using forward paths, and perspective as an all-knowing third person. The social values ​​are kinship values, values ​​of affection, cooperation, and mutual respect or respect. Based on data found from the novel, it can therefore be related to the Indonesian Language Lesson RPP in high school that is relevant enough to be used as teaching material for senior high school/equivalent.